THE URGENCY OF WOMEN'S LEADERSHIP INTEGRATION IN CAREER AND WORK LIFE BALANCE BASED ON THE EXPANSION OF GENDER EQUALITY IN INDONESIA - K.P. Suharyono S. Hadiningrat; Tasya Widya Krisnadi (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The dual role of women cannot be separated from their nature as women who can give birth, nurture children, take care of the household, serve their husbands, care for parents, and pursue careers in various fields they desire. To fulfill this dual role requires a high level of willpower and self-commitment, as well as support from various parties, especially from the husband and family. The achievement of Indonesian women's emancipation has shown significant progress, as evidenced by women reaching high positions such as President, Vice President, Ministers, Speaker of the House of Representatives, Governors, Vice Governors, CEOs, TNI/Police Generals, Managers, and more. This research design is a descriptive qualitative one that analyzes data regarding the variables of women's leadership integration, career, and work-life balance based on the expansion of gender equality. The qualitative descriptive method aims to discover and describe the phenomena of the studied variables narratively (non-numerical). The results show that the integration of women's leadership in career and work life balance is urgent to ensure a harmonious and productive relationship between both, to achieve the goals of organizations/institutions/companies. The challenge is not easy, and it needs to be strengthened in the dimensions of: a) Personal life enhancement of work—how personal and family life can improve someone's performance in an organization/institution/company, and b) Work enhancement of personal life—how work influences the quality of someone's personal and family life. From these conclusions, it is recommended that the government prepare adequate policies to develop women's leadership and strengthen access to education, health, and the economy, so they have sufficient social capital to develop a career that is harmonious with their personal and family interests.